Exacerbation of Thromboinflammation by Hyperglycemia Precipitates Cerebral Infarct Growth and Hemorrhagic Transformation. Issue 7 (July 2017) - Desilles, Jean-Philippe; Syvannarath, Varouna; Ollivier, Véronique; Journé, Clément; Delbosc, Sandrine; Ducroux, Célina; Boisseau, William; Louedec, Liliane; Di Meglio, Lucas; Loyau, Stéphane; Jandrot-Perrus, Martine; Potier, Louis; et al.
Abstract : Background and Purpose—: Admission hyperglycemia is associated with a poor outcome in acute ischemic stroke. How hyperglycemia impacts the pathophysiology of acute ischemic stroke remains largely unknown. We investigated how preexisting hyperglycemia increases ischemia/reperfusion cerebral injury. Methods—: Normoglycemic and streptozotocin-treated hyperglycemic rats were subjected to transient middle cerebral artery occlusion. Infarct growth and brain perfusion were assessed by magnetic resonance imaging. Markers of platelet, coagulation, and neutrophil activation were measured in brain homogenates and plasma. Downstream microvascular thromboinflammation (DMT) was investigated by intravital microscopy. Results—: Hyperglycemic rats had an increased infarct volume with an increased blood–brain barrier disruption and hemorrhagic transformation rate compared with normoglycemic rats. Magnetic resonance imaging scans revealed that hyperglycemia enhanced and accelerated lesion growth and was associated with hemorrhagic transformation originating from territories that were still not completely reperfused at 1 hour after middle cerebral artery recanalization. Intravital microscopy and analysis of brain homogenates showed that DMT began immediately after middle cerebral artery occlusion and was exacerbated by hyperglycemia. Measurement of plasma serotonin and matrix metalloproteinase-9 indicated that platelets and neutrophils were preactivated in hyperglycemic rats. Neutrophils from hyperglycemic diabetic patients showed increased adhesion to endothelial cells as compared with neutrophils from normoglycemic donors in flow chamber experiments. Conclusions—: We show that hyperglycemia primes the thromboinflammatory cascade, thus, amplifying middle cerebral artery occlusion–induced DMT. DMT exacerbation in hyperglycemic rats impaired reperfusion and precipitated neurovascular damage, blood–brain barrier disruption, and hemorrhagic transformation. Our results designate DMT as a possible target for reduction of the deleterious impact of hyperglycemia in acute ischemic stroke. Abstract : Supplemental Digital Content is available in the text.